Explaining Black Support for Donald Trump: Should We Rethink How We View Black Identity? - Arhin, Kofi (Université d'Ottawa / University of Ottawa, 2024)
African Americans have been the most loyal and consistent voters for the Democratic Party. The arrival of Donald Trump as the leader of the Republican Party came with a more radical stance within the party which does not favour minorities. However, Donald Trump did not see a decrease in African American support relative to past Republican Presidential candidates. This leads to the question of why these voters are not put off by Trump's rhetoric. This thesis explores African American support for Donald Trump and presents a new theory for the Black vote for the Republican Party. The argument put forth in this thesis is that Black Trump voters have different attachments to Black identity. The weaker one's attachment to Black identity is, the less likely they are to follow the socially expected political behaviour of most Black people. Their vote is then influenced by the primary identity which replaces Blackness. In the case of Black Trump voters, their primary identity is Christianity which causes them to follow the rules of Christian socialization over Black socialization. This in turn leads to a vote for the Republican Party, regardless of who the candidate is.
Keywords: Black Conservatism; Political Behaviour; Identity Politics; Sociology; American Politics; Political Psychology